ASSOCIATION BETWEEN NIH STROKE SCALE SCORE AND FUNCTIONAL OUTCOME IN ACUTE ISCHEMIC STROKE: NIH Stroke Scale Score - Fazal, Nadeem; Saif, Saba (Pakistan Armed Forces Medical Journal, 2014)
Objective: To evaluate the association between baseline national institutes of health stroke scale score and functional outcome after acute ischemic stroke. Study Design: Descriptive study. Place and Duration of Study: Medical unit-IV, Jinnah Hospital, Lahore, from May 2009 to October 2009. Patients and Methods: Patients who presented with stroke within 24 hours of onset of symptom and had a developing infarct on the CT-scan were further evaluated for neurological impairment using NIH stroke scale. The baseline NIHSS score was calculated using a proforma. Age of the patient, gender and time of presentation to the hospital was recorded. Follow-up was done on the 7th day of admission using Glasgow outcome scale (GOS). Results: Total number of subjects was 150. Good outcome (GOS=1-2) was noticed in those subjects who had a low baseline NIHSS score (0-6) while poor outcome (GOS=3-5) was noticed in those subjects who had a higher baseline NIHSS score (>16) (p value< 0.05). In cases who had a moderate score (7-15); the ratio of good outcome to bad outcome was almost 70:30. Likewise good outcome (GOS=1-2) was noticed in those subjects who were younger (less than 45years) while poor outcome (GOS=3-5) was noticed in the elderly (more than 45years) (p value< 0.05). Similarly patients who presented within 12hrs of symptom onset had a good outcome compared to those who presented after 12hrs (p value< 0.05). Conclusion: Baseline NIH Stroke Scale score is strongly associated with functional outcome after 1 week of acute ischemic stroke.